The role of the entrepreneur in today's society. Concerning the encyclical «Centessimus annus» - Pérez López, Juan Antonio (Mercurio Peruano, 2013)
The commentary of the encyclical leads to the reflection that the good businessman "is the one who leads people, the one who develops them as people helping them to grow in all aspects", and in line with the approaches proposed by John Paul II, business work is called to be a form of solidarity. Pérez López especially highlights the possibility of discovering skills and granting opportunities that are, like a football coach, characteristic of the executive's profile.